Improvement in Capacity of CDMA Mobile Communication Systems Through Two Level Call Admission Control - Bhaskar, Rekha (My University, 2008)
In the present work a comparative study of proposed Capacity Improvement of CDMA mobile communication system through two-level call admission control scheme carrying multimedia traffic. CDMA system is interference limited and has a soft capacity which changes depending on the interference felt at the base station at a given time. If interference increases beyond an acceptable level the system becomes unstable and may experience handoff failure and call blocking. Admitting a new call always increases the interference level in the system. Hence a robust method of accepting or blocking potential users i.e. a call admission control (CAC) technique is required. Even with efficient Admission Control, congestion could still be caused by the output powers are rapidly increased by the fast closed-loop power control until one or several transmitters are operating at their maximum power. The connections unable to achieve their required SIR levels are considered to be useless and are only adding interference to the system which caused high call blocking, handoff failure, high outage probabilities and low throughput Therefore two level CAC scheme is used to reduce congestion and increase the bandwidth by addition non real time call with real time call admission control scheme.The main advantages and drawbacks of the schemes were also highlighted.The two- level scheme fully utilizes the traffic characteristics of wireless multimedia ommunication; it assigns higher priority to the real-time traffic class in gaining ccess to the system resources and implements queuing of nonreal-time calls that cannot allocated resources at initial request instant. To ensure that nonreal-time calls are not starved of resources due to the higher priority given to real-time calls, the scheme also incorporates some reserved capacity for nonreal-time calls. For each traffic class, the scheme manages the uplink and downlink resources separately. Further, the scheme also manages the resources to new and handoff calls within each traffic class. Performance of the proposed two-level CAC scheme is analyzed using Markov chain theory to derive system performance metrics of call blocking, handoff failure, outage probability, and average throughput.
ME(EC)
Keywords: Direct Sequence Code Division Multiple Excess; Bit Error Rate